Nonclinical cardiovascular safety of pitolisant: comparing International Conference on Harmonization S7B and Comprehensive in vitro Pro-arrhythmia Assay initiative studies - Ligneau, Xavier; Shah, Rashmi R.; Berrebi-Bertrand, Isabelle; Mirams, Gary R.; Robert, Philippe; Landais, Laurent; Maison-Blanche, Pierre; Faivre, Jean-François; Lecomte, Jeanne-Marie; Schwartz, Jean-Charles (Wiley, 2017)
Background and purpose: We evaluated the concordance of results from two sets of nonclinical cardiovascular safety studies on pitolisant. Experimental approach: Nonclinical studies envisaged both in the ICH S7B guideline and Comprehensive in vitro Proarrhythmia Assay (CiPA) initiative were undertaken. CiPA-initiative studies included in vitro ion channels and stem cell-derived human ventricular myocyte studies as well as in silico modelling of results to simulate human ventricular electrophysiology. ICH S7B-recommended studies included in vitro hERG studies, in vivo dog study with follow-up investigations in rabbit Purkinje fibres and in vivo studies in the Carlsson rabbit proarrhythmia model. Key results: Both sets of nonclinical studies consistently excluded pitolisant from having clinically relevant QT-liability or proarrhythmic potential. CiPA studies revealed pitolisant to have modest calcium channel blocking and late I Na reducing activities at high concentrations, which resulted in reduction of dofetilide-induced early after-depolarisations (EADs) by pitolisantin ICH S7B studies. Studies in stem cell-derived human cardiomyocytes with dofetilide or E-4031 given alone and in combination with pitolisant confirmed these properties. In silico modelling confirmed that the measured ion channel effects are consistent with results from both the stem cell-derived cardiomyocyte and rabbit Purkinje fibre studies and categorised pitolisant as a drug with low torsadogenic potential. The results from the two sets of nonclinical studies correlated well with two clinical QT studies. Conclusions and implications: Our experience supports the CiPA initiative but suggests that sponsors should consider investigating drug effects on EADs and the use of proarrhythmia models when the results from CiPA studies are ambiguous.